An introduction to glutamine metabolism - Cruzat, Vinicius; Newsholme, P. (2017)
© 2017 by Taylor & Francis Group, LLC. Hlaziwetz and Habermann rst described glutamine as a molecule with biologically important properties in 1873. They suggested that the presence of ammonia (as NH4+), detected following hydrolysis of proteins, arose by degradation linked to amide groups from glutamine and asparagine (Mora 2012). About 10 years later, Schulze and Bosshard isolated glutamine from a natural source (beet juice), and Damodaran and his collaborators contributed to the rst description of glutamine metabolism. However, the number of studies investigating glutamine metabolism and links to intermediary metabolism increased following the early work of Sir Hans Adolf Krebs (1900-1981), who was responsible for some of the most important discoveries in metabolic biochemistry and physiology in the twentieth century (Nobel Prize in Physiology or Medicine in 1953).